IMPLIKASI TERBITNYA UNDANG-UNDANG NOMOR 23 TAHUN 2014 TERHADAP PEMBANGUNAN KESATUAN PENGELOLAAN HUTAN DI PROVINSI RIAU - Suwarno, Eno; Ratnaningsih, Ambar Tri; Insusanty, Enny (Wahana Forestra: Jurnal Kehutanan, 2016)
The issuance of the Law No. 23 of 2014 on Regional Government instead of Law No. 32 of 2004 carries implications for FMU development in the area. This study aims to (1) assess changes in the content of Law No. 23 of 2014 compared with the previous regulations in managing the affairs of the forestry sector; (2) assess the implications of these changes to the rules under which the current level is the reference FMU development; and (3) assess the implications of these changes to the processes of FMU development in Riau Province. The study was conducted in December 2014 -May 2015, with research sites in the city of Pekanbaru and the district of Kampar, Riau Province. The method used is the content analysis of the rules and interviews with some stakeholders. The substantial changes of the Law No. 32/2004 to Law No. 23/2014, in the new regulations authorizes the establishment of the organization KPHL / KPHP everything under the authority of the provincial government, no longer under the authority of district governments. The implications of the transfer of authority, the regulations that the legal basis and the establishment of institutions KPHL / KPHP i.e. the Government Regulation (PP) No. 38/2007 and Rule of th e Interior Minister (Permendagri) No. 61/2010 can not be a reference again. In addition it also affects the initiative and formation process KPHL / KPHP by Regency stagnated.